Regulators of thymic stromal lymphopoietin production by human adipocytes. (December 2020) - Ma, Loretta; Zhen, Jamie; Sorisky, Alexander
Highlights: TSLP is produced by subcutaneous human adipocytes in response to TSH, IL-1β, or IFN-γ. TSLP responses to TSH were dependent on PKA and ERK1/2 signaling. TSLP responses to IL-1β were dependent on IKKβ signalling. Intra-abdominal omental adipocytes also displayed TSLP responses. Abstract: Thymic stromal lymphopoietin (TSLP) is a cytokine that is known to play a role in inflammatory conditions, especially asthma and atopic dermatitis. It is also recognized to be expressed in human adipose tissue. TSLP production from human adipocytes is stimulated by thyroid-stimulating hormone (TSH). This study aimed to identify TSH-dependent signaling routes that regulate TSLP, to determine if TSLP production is stimulated by other cytokines (IL-1β and TNF-α), and to examine if TSLP production depends on the adipose depot. Human abdominal differentiated adipocytes were stimulated with TSH, IL-1β, or TNF-α. Activation of cell signaling kinases was measured by phospho-immunoblot analysis, and TSLP in medium was assessed by ELISA. TSLP responses from abdominal subcutaneous and omental adipocytes were compared. TSH-stimulated TSLP secretion from subcutaneous adipocytes was enhanced by IBMX (raises cAMP levels) and was blocked by UO126 (inhibitor of MEK1/2-ERK1/2). TSLP secretion was stimulated by IL-1β and by TNF-α. SC-514 (inhibitor of IKKβ/NF-κB) only reduced the former. There was no effect of SB203580 (p38 MAPK inhibitor) or SP600125 (JNK inhibitor) on the stimulation by TSH, IL-1β or TNF-α. Interferon-γ inhibited TSLP responses to TSH, IL-1β, and TNF-α; IL-4 only blocked the response to TNFα. Intra-abdominal omental adipocytes also release TSLP in response to TSH, IL-1β, and TNF-α. We conclude TSLP is produced by human differentiated adipocytes derived from subcutaneous or omental depots in response to a variety of agonists. Further studies will be needed to understand what role it may play in adipose biology.